Analisis Pendapatan Food Vlogger dari Konten Review yang Bersifat Dekstruktif Perspektif Hukum Ekonomi Islam - Masidah Masidah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the permissibility status of income earned by Food Vloggers from destructive review content within the perspective of Islamic economic law. The background of this study is based on the increasing phenomenon of Food Vloggers on social media, who not only function as a medium of information and promotion but also have the potential to cause harm to business actors through excessive, misleading, or defamatory review content. This research employs a normative legal approach with a fiqh muamalah perspective by examining Islamic principles such as honesty (sidq), justice (‘adl), trustworthiness (amanah), and the prohibition of harm (dharar). The findings indicate that review activities are fundamentally permissible in Islam as long as they do not violate sharia principles. However, if the review content is destructive and causes harm to others, it contradicts the principle of la dharar wa la dhirar as well as the objectives of sharia (maqasid al-shariah), particularly in protecting honor (hifz al-‘ird) and wealth (hifz al-mal). Therefore, income derived from such content cannot be categorized as lawful (halal) income.